Interpretation methods and holistic analysis of bioethics’ cases - Schmidt, Ludwig (Acta Bioethica, 2008)
The author of this report offers a phenomenological method together with an hermeneutic comprehension which stems from an anthropological and ethic paradigm that allows to systematize and interpret different situations in three stadiums: plannign, appraisal (social, technique, juridical and bioethics’) and the delemma’s conclusions and implications. The scherme constitutes a rational way that helps all actors to arrive at the proper object of their discipline starting from a plurality of positions and in an integral and objetive manner. It studies and derives, by means of a logical process of a systemic concatenation of ideas, forms and experiences, respecting the beliefs and cultures that are present and establishing the minimum ethics.